Electronic Fund Transfers and Business Growth Among SMEs in Kabale Municipality, Kabale District - Martin Muhumuza (Uganda Christian University, 2025)
The study looked into how small and medium-sized businesses in Kabale municipality's Kabale district grew in relation to electronic fund transfers. The study's three primary goals were to determine the relationship between mobile money use and business expansion among SMEs in Kabele Municipality. Analyze how automated teller machines affect SMEs' access to financing in Kabale Municipality and how debit cards affect their ability to expand their businesses. The study's results were reported using an across-sectional research design. 300 SMEs in the manufacturing, trade, and service sectors were included in the study. Purposive methods and basic random sampling were used to choose a sample of 169 SMEs. Questionnaires and an interview guide were used to gather data, and both descriptive and multiple regression analyses were used for analysis. The results showed a correlation between the use of EFTs and business growth, with EFTs explaining as little as 7.0% of the variance in business growth. While using debit cards and ATMs has no discernible impact on business growth, using mobile money has a big impact. According to the study's findings, there is very little correlation between EFT and business growth among SMEs in Kabele Municipality. Bankers should therefore try to contact SMEs and offer them incentives to open bank accounts, allowing them to use debit cards and ATMs. The study highlighted the connection between the expansion of SMEs in Kabale Municipality and electronic money transfers. With the advent of new financial inclusion strategies, EFT emerged as a cutting-edge money transfer technique. As a crucial instrument for advancing the objective of financial inclusion, electronic funds transfer services have been rapidly implemented throughout emerging countries, particularly by small and medium-sized enterprises. This has a significant impact on the commercial and economic sectors, as well as the financial industry. As a result of these innovative approaches, which enabled the unbanked to enter the banking industry, SMEs prospered. This chapter covers the background, goals, and conceptualization of EFT, as well as the expansion of SMEs.